Depiction of a deity on the wall - Temples of India Project Team (Jio Institute, 2024)
The Mandakini Kund reflects the vast skies, with birds in flight, and the temple spires creating a peaceful scene. One can see the depiction of a deity on the wall, which may have been a later addition.